Pengaruh Kepemimpinan Kepala Sekolah dan Efikasi Diri Giuru terhadap Kinerja Guru - Nuzilal Haq; Imam Tholkhah; Amie Primarni (LPPM Institut Nasional Laa Roiba Bogor, 2020)
The phenomenon that occurs based on data from the Bogor District Education Office, regarding Elementary School Teachers in Cluster IV, Pamijahan sub-district, Bogor Regency, turns out that the performance of elementary school teachers is still low. This is shown from the average results of the performance evaluation of elementary school teachers in Cluster IV Pamijahan sub-district by the Bogor District Government in collaboration with the Bogor District Education Office in 2016 showing that the performance of elementary school teachers in Cluster IV Pamijahan sub-district Bogor Regency is relatively low at an average of 41 72%. If this problem does not get attention and is left by educators including the principal, then the quality of the learning process will remain low, making it impossible for efforts to improve the quality of education to achieve significant results. This study aims to determine and find the relationship between the principal's leadership and teacher's self-efficacy both together and partially with the performance of teachers in Cluster IV Pamijahan sub-district. This study uses correlational research methods to solve problems. The population in this study were all elementary school teachers in Cluster IV, Pamijahan sub-district, Bogor Regency with a total of 283 people. The sample in this study was taken with Stratifield Proportional Random Sampling totaling 166 respondents from 34 public elementary schools in Cluster IV Pamijahan sub-district. Data collection techniques for all variables using a questionnaire. Data analysis techniques using correlation analysis, multiple correlation, regression, multiple regression and coefficient of determination with the prerequisite test analysis is the normality test. Based on the results of the study it can be concluded: (1) Based on the results of the test of the significance of the correlation shows that t arithmetic > t table (2.268> 1.981) Thus the research hypothesis which states there is a relationship between the leadership of the school principal and the performance of elementary school teachers in group IV Pamijahan District is proven to be true. (2) Based on the results of testing the significance of the correlation shows that t arithmetic> t table (2.767> 1.981) Thus the research hypothesis which states that there is a relationship between self-efficacy and the performance of elementary school teachers in cluster IV Pamijahan District tested the truth. (3) Based on the results of the significance test of multiple linear regression equations, Fcount is 3.78 while Ftable for denominator 2 and numerator 109 for confidence level α = 0.05 is 3.08 which means the value of Fcount> Ftable (3.78> 3, 08). This shows that Ho was rejected, meaning Ha who stated there was a positive relationship between the principal's leadership and the teacher's self-efficacy together with the teacher's performance was acceptable Keywords: Teacher Performance, Principal Leadership and Teacher Self-Efficacy